Payment Methods and Coping Strategies for Health Care Costs by Patients with Chronic Diseases in a Low-Middle Income Country - Mariere, U I; Ogaji, D S; Obikeze, O O; Adesina, A D; Babatunde, S (West African journal of medicine, 2025)
Chronic diseases contribute the highest to disease burden and deaths worldwide and require long-term access to health care. This study identified the payment methods and coping strategies for healthcare costs by patients with chronic diseases using public health facilities in Yenagoa, Bayelsa State, Nigeria. Three hundred and thirty-nine (339) adult patients, being managed for chronic conditions (Hypertension, Diabetes mellitus, Tuberculosis & HIV), were randomly selected from three specialist hospitals that are the major providers of specialized care for patients with chronic diseases in the State. Data on sociodemographic characteristics, morbidity patterns, household financing and coping with health expenditure were collected. Chi-squared test was used to identify significant associations. A p-value 0.05 was considered significant. Majority were females 211(62%) and about a third were not working 113(33.3%). To pay for their chronic disease healthcare expenses, 268 (79.1%) paid out-of-pocket while 71 (20.9%) used social health insurance. Among the 120 (35.4%) patients who subscribed to a health insurance program, about 2 in 5 still paid out-of-pocket. Missing a clinic visit 145(42.8%) was the common coping strategy followed by patients having to forfeit necessities 113(33.3%) to cope with their healthcare costs. The type of chronic disease was statistically associated with payment methods adopted by patients (p<0.01). Most patients with chronic diseases rely on out-of-pocket payments for healthcare expenditures including patients with health insurance coverage. This has necessitated households to adopt coping strategies, found to be economically distressing, to source funds for healthcare needs. Targeted programmes are needed for patients with chronic diseases to enhance financial risk protection.